Kontribusi dan efektivitas pajak reklame terhadap pendapatan asli daerah di Kabupaten Ogan Komering Ulu periode tahun 2013 – 2017 - Novegya Ratih Primandari; Emi Dahlia (Penerbit Goodwood, 2020)
Purpose: The purpose of this study was to determine how much the contribution and effectiveness of the Advertisement Tax on Local Original Revenue in Ogan Komering Ulu Regency for the Period of 2013 - 2017. Research methodology: The analytical tool used is quantitative descriptive using contribution analysis and effectiveness analysis. Results: The results shows that the contribution of advertisement tax to regional original income is very low. At the same time, the effectiveness analysis shows that the advertisement tax of regional original income is very effective. Limitations: This study is limited to analysis of the contribution and effectiveness of advertisement tax on Local Original Revenue, which in fact there are still many other tax levies that contribute to Local Original Revenue in OKU Regency. Contribution: This research can be used as a reference in the link of economic research in the area of ??regional development planning and can be used as a material consideration for local governments to pay more attention to the collection of advertisement tax as one of the main sources of Local Original Revenue. Keywords: Contribution, Effectiveness, Bill Tax, Local Original Revenue